2021
DOI: 10.1097/eja.0000000000001521
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of a machine-learning algorithm to predict intra-operative hypotension with noninvasive arterial pressure waveforms

Abstract: BACKGROUND Intra-operative hypotension is associated with adverse postoperative outcomes. A machine-learning-derived algorithm developed to predict hypotension based on arterial blood pressure (ABP) waveforms significantly reduced intra-operative hypotension. The algorithm calculates the likelihood of hypotension occurring within minutes, expressed as the Hypotension Prediction Index (HPI) which ranges from 0 to 100. Currently, HPI is only available for patients monitored with invasive ABP, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 28 publications
1
29
1
Order By: Relevance
“…A possible explanation is that we applied a different type of analysis, compared to previous trials. As described in detail by Wijnberge et al [ 22 ], the forward analysis also performed in this study, relates better to clinical practice since an increased HPI value is the starting point, rather than the hypotensive event itself. Differences in the analysis could have led us to label certain timeframes differently than we would have in the case of a backward analysis, which presumably yields other results.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…A possible explanation is that we applied a different type of analysis, compared to previous trials. As described in detail by Wijnberge et al [ 22 ], the forward analysis also performed in this study, relates better to clinical practice since an increased HPI value is the starting point, rather than the hypotensive event itself. Differences in the analysis could have led us to label certain timeframes differently than we would have in the case of a backward analysis, which presumably yields other results.…”
Section: Discussionmentioning
confidence: 92%
“…To date, performance of the HPI has been externally and clinically validated in five observational studies and three randomized controlled trials (RCTs) [ 28 ]. In non-cardiac surgical patients, external validation has been done on invasive [ 23 ] and non-invasive [ 22 , 24 ] arterial waveform data. All these three trials reported sensitivity and specificity > 85%, based on HPI values 5 min prior to the event (in the case of a backward analysis), or based on an HPI value of 85 (in the case of a forward analysis).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, we showed that HIF-1α is not significantly up-regulated in both groups and is not dependent on the number and duration of hypotensive events. Subunit α is oxygensensitive, during normoxia is associated with von Hippel-Lindau (VHL) protein, which is responsible for the induction of its proteasome degradation [18,19]. Therefore, in normoxia, the half lifetime of HIF-1α is greatly shorted than in hypoxia conditions [20], as low pressure of oxygen is responsible for blocking the binding of VHL and HIF-1α and its degradation is then inhibited [21].…”
Section: Discussionmentioning
confidence: 99%